(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
The use of drugs reaches each day greater visibility in society and currently enhances strong discussions about which would be the best ways to deal with such subject: adoption of a criminal police is even more competitive or is human related it is driven to protection and care towards the user. Among such a discussion, there may be issues raised such as decriminalization based on autonomy will and on constitutional rights such as freedom, intimacy and privacy. Upon all that, there is an issue raised: in legal terms it is in place a fragile distinction – in need of objective criteria – between a user who is drug trafficker should be positioned in the order of the day, but it ends up being lost in such a universe surrounded by questioning and social or legal changes in place.